A cationic fluorescent probe for BF4− and PF6− anions by aggregation self-assembly: An efficient approach to recognition of anions in aqueous solution. (April 2019) - Gong, Xue; Zhang, Qi-Long; Zhang, Sheng; Xia, Yu; Bai, Qinghong; Chen, Shiyan; Ni, Xin-Long
Abstract: Anion recognition and sensing are of interest because anions play important roles in biological and environmental systems. However, there are major challenges to be overcome in developing highly selective probes for anions in water because of the strong hydration of anions. Here, a new type of anion fluorescent probe based on the π-conjugated positively charged pyridinium derivatives was prepared. It displayed highly selective fluorescence sensing for BF4 − and PF6 − ions in neutral water solution and in living cells. This probe exhibited a novel fluorescent detection signal output for targeting anions through the aggregation self-assembly aided by multiple non-covalent interactions triggered by anion recognition, as well as the effect of the desolvation of charge-diffuse larger anions in aqueous media according to the Hofmeister bias. Fluorescence microscopy studies of HeLa cells suggested that both of the cationic probes and the target anions could enter the cells and give rise to the specific in vivo fluorescence response signal. Graphical abstract: A new type of anion fluorescent probes based on the π-conjugated positively charged pyridinium derivatives, which displayed highly selective fluorescence sensing for lager weak BF4 − and PF6 − ions in neutral solution and living cells. Highlights: This probe displayed highly selective fluorescence sensing for BF4 − and PF6 − ions in neutral solution and living cells for the first time. Fluorescence images suggest that larger weak anions BF4 − and PF6 − could permeate the plasma membrane of the cells and enter the cells. Isothermal titration calorimetry experiment indicate that the desolvation of charge-diffuse larger anions in aqueous media play an important role in the sensing procedure of the target anions according to the Hofmeister bias. A novel design strategy for developing fluorescent probe for anions in aqueous solution has been demonstrated.